2019
DOI: 10.1007/s10278-019-00274-4
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning for Low-Dose CT Denoising Using Perceptual Loss and Edge Detection Layer

Abstract: Low-dose CT denoising is a challenging task that has been studied by many researchers. Some studies have used deep neural networks to improve the quality of low-dose CT images and achieved fruitful results. In this paper, we propose a deep neural network that uses dilated convolutions with different dilation rates instead of standard convolution helping to capture more contextual information in fewer layers. Also, we have employed residual learning by creating shortcut connections to transmit image information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 43 publications
2
89
0
Order By: Relevance
“…This study revealed that some of the LDCT restoration applications reported in [ 20 , 23 , 71 , 73 ] followed the same ResNet model published by Zhang et al [ 86 ]. Accordingly, a cascaded ResNet-based LDCT restoration model published by Wu et al [ 73 ] has the strength to restore the noise patterns that would rarely encounter in the training datasets via iterative cascaded learning.…”
Section: Architecturessupporting
confidence: 63%
See 2 more Smart Citations
“…This study revealed that some of the LDCT restoration applications reported in [ 20 , 23 , 71 , 73 ] followed the same ResNet model published by Zhang et al [ 86 ]. Accordingly, a cascaded ResNet-based LDCT restoration model published by Wu et al [ 73 ] has the strength to restore the noise patterns that would rarely encounter in the training datasets via iterative cascaded learning.…”
Section: Architecturessupporting
confidence: 63%
“…Residual Network (ResNet): Stacking more layers in the CNN model is one of the basic techniques for improving the performance of the CNN model. However, increasing the depth of the network will always not influence CNN positively due to the issue called gradient diffusion [ 20 , 50 ]. Also, gradient diffusion might result in failures in network training.…”
Section: Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Asa solution to this problem, many methods have been designed for denoising LDCT images. These methods generally fall into three categories: techniques based on sinogram filtering, iterative reconstruction, and post-reconstruction image processing [8][9][10]. In addition, denoising algorithms using artificial deep neural networks have demonstrated impressive performance capabilities in this context [8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 – 14 ] Noise reduction techniques using CNN have also been proposed in the field of medical imaging. [ 15 ] Several studies have shown that deep learning-based super-resolution or denoise approaches were successfully applied to low-quality MR images to shorten imaging time. [ 16 , 17 ] However, few studies have shown the impact of the deep learning-based approaches that improve the image quality of SSTSE image.…”
Section: Introductionmentioning
confidence: 99%